Influence of Forest Walking on Blood Pressure, Profile of Mood States and Stress Markers from the Viewpoint of Aging - Horiuchi, Masahiro; Endo, Junko; Akatsuka, Shin; Uno, Tadashi; Hasegawa, Tatsuya; Seko, Yoshiyuki (Journal of Aging and Gerontology, 2013)
This study investigated the influence of forest walking on blood pressure (BP), profile of mood states (POMS) and salivary cortisol in both young and aged people. Twenty-three young people (Men=11, Women=12) with a mean age of 22 yrs and twenty-five aged people (M=10, W=15) with a mean age of 59 yrs participated in this study voluntarily. Each participant walked about three hours in the forest according to their comfortable walking pace. After forest walking, systolic BP (SBP) and mean BP (MAP) had significantly decreased in aged people (-10±3 mmHg in SBP, and -5±2 mmHg in MBP, P<0.05, respectively) while remained unchanged in young people. The scores for the “tension-anxiety” and “confusion” subscales of POMS were significantly improved in both young and aged people; moreover, the score for the “anger–hostility” subscale in aged people was also improved significantly. Salivary cortisol significantly decreased in young people (-0.22±0.03?g/dl, P<0.05) and had a tendency to decrease in aged people (-0.05±0.03?g/dl, P=0.099). BP variables at baseline were associated with the changes in BP variables (r=0.575 in systolic BP, r=0.581 in diastolic BP, r=0.582 in MAP, and r=0.582 in pulse pressure), respectively. Furthermore, the baseline salivary cortisol was also related to the forest walking-induced changes in that value (r=0.882). Thus, people with higher BP and higher stress markers may show greater effects from forest walking. Collectively, these results suggested that forest walking may have the possibility to reduce resting BP, mental stress and stress markers in both young and aged people; moreover, significant deceases in BP of aged people indicate that forest walking can be an important and novel exercise therapy if undertaken at a comfortable pace.